Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia - Ng, Heok Hee (Zootaxa, 2004)
A new species of bagrid catfish of the genus Rita is described from the Indus River drainage in South Asia. Rita macracanthus differs from all congeners in having a unique combination of the following characters: dorsal spine reaching to middle of adipose-fin base; pectoral-spine length 28.7 30.0% SL; depth of caudal peduncle 7.6 8.4% SL; maximum length of premaxillary tooth band 4.8 6.4 times its maximum width; eye diameter 6.9 8.7% HL; interorbital distance 39.4 44.1% HL; dorsal surface of head between eyes and supraoccipital covered with thin skin wherein the underlying bone is visible; two distinct vomerine tooth patches with rounded peg-like teeth. The new species has been identified up until now as Rita rita, but is distinguished from that species in having longer dorsal and pectoral spines, a more slender caudal peduncle, and a longer premaxillary tooth band.